2011
DOI: 10.1002/app.34408
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and studies of blue light emitting polymers containing triphenylamine‐substituted fluorene and diphenylanthracene moiety

Abstract: Photoluminescent (PL) polymers containing triphenylamine-substituted fluorene and diphenylanthracene (DPA) units were synthesized by aromatic nucleophilic substitution reaction. The light emitting polymers (LEPs) contains hole-transporting triphenylamine (TPA) groups at the C-9 position of fluorene and DPA-emitting segments in the main chain. The obtained polymers were soluble in various organic solvents and thermally stable. The synthesized polymers were successfully characterized by elemental analyses, FTIR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…The polydispersity index (PDI) was calculated using number average molecular weight (Mn) and weight average molecular weight (Mw) approximately comes around 1 indicating uniform and one length of polymers. [13] This observation indicated that the polymers synthesized in the present investigation were nonbranching. The combination of GPC and NMR was used to confirm the structures and molecular weights of polymers by calculating the ratio of the integration of protons from the NMR spectrum of the polymers.…”
Section: Gel Permeation Chromatography (Gpc)mentioning
confidence: 51%
See 3 more Smart Citations
“…The polydispersity index (PDI) was calculated using number average molecular weight (Mn) and weight average molecular weight (Mw) approximately comes around 1 indicating uniform and one length of polymers. [13] This observation indicated that the polymers synthesized in the present investigation were nonbranching. The combination of GPC and NMR was used to confirm the structures and molecular weights of polymers by calculating the ratio of the integration of protons from the NMR spectrum of the polymers.…”
Section: Gel Permeation Chromatography (Gpc)mentioning
confidence: 51%
“…The structural characterization of the monomers was done by 1 H, 13 C NMR, and FTIR spectroscopy. The first significant feature of the infrared spectra of polymers ( Figure S3) was the absence of absorption peaks in the region 3400 cm À 1 indicating completion of polymerization and termination of the terminal hydroxy group of alkyl substituted DPA monomers.…”
Section: Structural Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that the electronic strength of the substitution (electron‐donating or electron‐withdrawing nature) affects the electrochemical properties of materials containing the TPA moiety. According to the Hammet equation, electron‐donating groups, mainly at the para orientation of the TPA unit, exert a driving force in radical cation formation and stabilize it efficiently . However, electron‐withdrawing substituents have the opposite impact .…”
Section: Introductionmentioning
confidence: 99%